Ecobrick sebagai Sarana Mewujudkan Masyarakat Inklusif - Trisniawati Trisniawati; Dinar Westri Andini; Wahyu Setya Ratri (Universitas Mathla'ul Anwar Banten, 2019)
ECOBRICK AS A MEANS OF CREATING AN INCLUSIVE SOCIETY. This study aims to describe how ecobrick is a means to realize an inclusive society. This is expected to overcome environmental problems, especially inorganic waste management through ecobrick. This research was conducted in the villages of Jatirejo, Lendah, Kulon Progo, Yogyakarta. Data analyzed in the form of primary data, namely questionnaire on the implementation of activities and the results of interviews with society. The questionnaire made for the evaluation of activities consisted of material, speakers, and facilities and infrastructure. The results of the study show that the community can participate in ecobrick activities well. In the evaluation results of the material as many as 17 diffables present in the indicator 1. the material can be received as much as one diffable gives a score of 1, eight diffables give a score of 3, and eight diffables give a score 4. On the indicator 2. the material is useful for participants with one diffable score 2, eight diffables gave a score of 3, and eight diffables gave a score of 4. In the indicator 3. the material was distributed to participants as many as nine diffables gave a score of 3 and eight diffables gave a score 4. In indicator 4. there were examples of 8 material diffables giving score 3 and nine diffables give a score of 4. In indicator 5. the speaker clearly stated that one diffable gave a score of 1, 12 diffables gave a score of 3, and four diffables gave a score of 4. On indicator 6. delivering interesting material as much as one diffable gave a score of 2, 11 diffables gave a score of 3, and five diffables gave a score of 4.